LncRNA BCAR4 promotes liver cancer progression by upregulating ANAPC11 expression through sponging miR-1261 - Zhang, Yu (Int J Mol Med, 2020)
Liver cancer is a malignant tumor that occurs in the liver and can be divided into primary and secondary liver cancer. Long non-coding RNA (lncRNA) breast cancer anti-estrogen resistance 4 (BCAR4) has been demonstrated to promote the development of various types of cancer. However, the function of lncRNA BCAR4 in liver cancer remains unclear. In the present study, the expression of lncRNA BCAR4 was notably elevated in liver cancer compared with adjacent non-tumor tissues. Functional in vitro assays demonstrated that knockdown of lncRNA BCAR4 inhibited the proliferation, migration and invasion of Huh-7 cells. In addition, lncRNA BCAR4 was demonstrated to directly bind to microRNA (miR)-1261, and miR-1261 expression negatively correlated with the expression of lncRNA BCAR4. Through bioinformatics analysis, lncRNA BCAR4 was predicted to target anaphase-promoting complex subunit 11 (ANAPC11) through miR-1261. In addition, the results demonstrated that lncRNA BCAR4 increased the expression of ANAPC11 by inhibiting miR-1261 expression. Consistently, overexpression of ANAPC11 or inhibition of miR-1261 significantly rescued liver cancer cell proliferation induced by knockdown of lncRNA BCAR4. Collectively, the results of the present study demonstrated that lncRNA BCAR4 may promote liver cancer development by directly binding to miR-1261 and targeting ANAPC11.